Scoping review of systematic reviews of complementary medicine for musculoskeletal and mental health conditions. Issue 10 (15th October 2018) - Lorenc, Ava; Feder, Gene; MacPherson, Hugh; Little, Paul; Mercer, Stewart W; Sharp, Deborah
Abstract : Objective: To identify potentially effective complementary approaches for musculoskeletal (MSK)–mental health (MH) comorbidity, by synthesising evidence on effectiveness, cost-effectiveness and safety from systematic reviews (SRs). Design: Scoping review of SRs. Methods: We searched literature databases, registries and reference lists, and contacted key authors and professional organisations to identify SRs of randomised controlled trials for complementary medicine for MSK or MH. Inclusion criteria were: published after 2004, studying adults, in English and scoring >50% on Assessing the Methodological Quality of Systematic Reviews (AMSTAR); quality appraisal checklist). SRs were synthesised to identify research priorities, based on moderate/good quality evidence, sample size and indication of cost-effectiveness and safety. Results: We included 84 MSK SRs and 27 MH SRs. Only one focused on MSK–MH comorbidity. Meditative approaches and yoga may improve MH outcomes in MSK populations. Yoga and tai chi had moderate/good evidence for MSK and MH conditions. SRs reported moderate/good quality evidence (any comparator) in a moderate/large population for: low back pain (LBP) (yoga, acupuncture, spinal manipulation/mobilisation, osteopathy), osteoarthritis (OA) (acupuncture, tai chi), neck pain (acupuncture, manipulation/manual therapy), myofascial trigger point pain (acupuncture), depression (mindfulness-based stress reduction (MBSR), meditation, tai chi, relaxation), anxiety (meditation/MBSR, moving meditation, yoga), sleep disorders (meditative/mind–body movement) and stress/distress (mindfulness). The majority of these complementary approaches had some evidence of safety—only three had evidence of harm. There was some evidence of cost-effectiveness for spinal manipulation/mobilisation and acupuncture for LBP, and manual therapy/manipulation for neck pain, but few SRs reviewed cost-effectiveness and many found no data. Conclusions: Only one SR studied MSK–MH comorbidity. Research priorities for complementary medicine for both MSK and MH (LBP, OA, depression, anxiety and sleep problems) are yoga, mindfulness and tai chi. Despite the large number of SRs and the prevalence of comorbidity, more high-quality, large randomised controlled trials in comorbid populations are needed.